Phosphate coprecipitation affects reactivity of iron (oxyhydr)oxides towards dissolved iron and sulfide. (15th March 2022) - Kraal, Peter; van Genuchten, Case M.; Behrends, Thilo
Abstract: Iron (Fe) cycling exerts strong control on the mobility and bioavailability of the key nutrient phosphate (PO4 ) in soils and sediments. Coprecipitation of PO4 is known to alter the structure of Fe (oxyhydr)oxides (FeOx), however the environmental fate of PO4 -bearing FeOx is not well-understood. Here, PO4 -bearing FeOx with 9 mol% coprecipitated PO4 were prepared by Fe(III) hydrolysis and Fe(II) oxidation in the presence of dissolved PO4, in addition to pure FeOx synthesized in PO4 -free solutions. The pure and PO4 -bearing FeOx were subsequently exposed to different concentrations of dissolved Fe(II) and sulfide (2 and 10 mmol L −1 ). Mineral transformations and the fate of PO4 were tracked over 7–14 days with wet chemical techniques (including sequential Fe and S extraction) and synchrotron-based Fe K-edge X-ray absorption spectroscopy. Coprecipitation of PO4 affected the rate and extent of FeOx transformation differently for Fe(II) and sulfide. Poorly-ordered PO4 -bearing FeOx was preserved in the presence of dissolved Fe(II) while pure ferrihydrite was nearly completely transformed into goethite over 7 days. By contrast, coprecipitation of PO4 rendered FeOx more reactive towards sulfide compared to pure FeOx. Reaction with dissolved sulfide resulted in the formation of non-sulfidized Fe(II) or Fe(II) sulfide under high and low Fe/sulfide ratio, respectively. Under low Fe/sulfide ratio, Fh and PO4 -bearing, poorly-ordered FeOx were nearly completely sulfidized after 14 days. Sulfidation of FeOx led to efficient release of PO4 into solution, and at low Fe/sulfide ratio more PO4 was released than expected based on the extent of Fe sulfidation. The results suggest feedback mechanisms of environmental relevance: coprecipitation of strongly-sorbing species such as PO4 disrupts FeOx structure, which affects FeOx reactivity and the overall nutrient or contaminant retention capacity of soils or sediments differently depending on the ambient redox conditions. Specifically, the switch from reducing to sulfidic conditions may be associated with the disproportionate release of nutrients and contaminants.